The effect of the dates of shoot selection and shoot tip removal on the growth of William’s pear trees - Dremák, Péter; Kocsisné Molnár, Gitta; Szentpéteri, Tamás (Acta Agraria Debreceniensis, 2005)
Increasing the intensity of production in the case of pear can be the solution to satisfy the market demand forr high-quality fruit. The aims in this technology are the canopy treatments and the maintainance of consistently high quality yields in the long run. The experiments were performed with cv. William’s pear, a cultivar grown on large areas in Hungary. To create the optimal canopy shape for earlier fruiting, we performed shoot selection and the cutting back of shoot tips. Our results show, that both pruning methods – applied at 3 different dates – decreased the number of short fruiting parts (spurs), and increased the number of vegetative shoots. The sole exception was from this the effect of shoot tip removal when done at the earliest date.